Environmental influences on terminal migration behaviour of Chinook salmon in Cowichan Bay, British Columbia - Kelsie A. Murchy; William D.P. Duguid; Jamieson B. Atkinson; Jessica Qualley; Katie G. Innes; Hailey L. Davies; Bridget Maher; Francis Juanes (Fisheries Research, 2026)

Muscle Ageing and Sarcopenia Study (MASS) Lifecourse: a valuable resource for understanding skeletal muscle ageing - Rachel Cooper; Christopher Hurst; Holly Syddall; Helen Atkinson; Jonathan G. Bunn; Daniela Carpinelli; Antoneta Granic; Susan J. Hillman; Emma Grace Lewis; Claire McDonald; Katie Sloan; Karen Suetterlin; et al. (GeroScience, 2026)

Genomic Architecture of Inbreeding Depression Associated With Hatching Failure in an Endangered Parrot - Yasmin Foster; Stefanie Grosser; Brodie J. Foster; Nicolas Dussex; Aimee Stubbs; Ludovic Dutoit; Theo Atkinson; Fiona Robertson; Ken G. Dodds; Rudiger Brauning; Jeanne M. E. Jacobs; John C. McEwan; et al. (Molecular Ecology, 2026)
Conservation management of endangered species increasingly relies on genomic approaches to understand how long‐term small population sizes affect the fitness of extant individuals. However, despite the growing investment in genomic resources by conservation programmes, the impact that sequencing methods have on the ability to detect inbreeding‐related phenomena has been largely overlooked. Here, we compare the use of whole‐genome and reduced‐representation sequencing approaches in 148 individuals of the critically endangered parrot, the kākāpō ( Strigops habroptilus ), to assess inbreeding and its effects on female reproductive success. We explore how sequencing choice influences the identification of long stretches of homozygosity across the genome (runs of homozygosity, ROH), and compare the conservation implications of the results produced by each method. Both whole‐genome and reduced‐representation sequencing approaches provided comparable estimates of genome‐wide inbreeding ( F ROH ) and revealed consistent effects on egg hatching success, suggesting that reduced‐representation sequencing is capable of detecting inbreeding depression in wild populations under certain conditions. Whole‐genome sequencing enabled chromosome‐level inbreeding analyses, which revealed no strong evidence of chromosome‐specific effects beyond the genome‐wide signal. These results suggest that inbreeding depression in kākāpō reflects small effects across many chromosomes rather than strong effects on only a few, and that the primary benefit of whole‐genome sequencing lies in improving the precision of genome‐wide inbreeding estimates rather than identifying chromosome‐specific effects. Our findings highlight the distinct benefits of each sequencing approach in conservation, particularly within the context of resource limitations.

Locomotion Reveals Contrasting Responses in Body Mass‐Scaling of Metabolic Rates Between Winged and Wingless Arthropods - Vojsava Gjoni; Hanrong Tan; Andrew G. Hirst; Pavel Kratina; David Atkinson (Ecology Letters, 2025)
Metabolism fuels fundamental biological processes and commonly scales with body mass with an exponent, b , between 2/3 and 1. We, here, explore how differences in physical activity can reveal contrasting interspecific metabolic scaling between major groups of arthropods. The Metabolic‐level Boundaries Hypothesis predicts that increased behavioural activity increases b . We test this hypothesis by comparing b during flight, non‐flight locomotion, and rest in winged and wingless insects, and spiders. We find that interspecific b values increase with activity only with flight in winged insects which co‐occurs with a substantial flight‐related rise in metabolic level. Spiders show a shallower interspecific metabolic scaling relative to insects, potentially reflecting slower life‐history strategies with increasing body size. Consequently, large resting or walking insects consume 6–15 times more oxygen than do spiders of corresponding size and activity level. These fundamental differences offer new insights into the evolutionary dynamics of arthropod energetics.

Establishing a basis for recognising marine ‘other effective area-based conservation measures’ (OECMs) in South Africa - SP Kirkman; P Kowalski; SD Holness; LJ Atkinson; R Brand; L Dunga; TP Fairweather; T Goldman; D Marnewick; J Nhleko; R Peter; C Smith; et al. (African Journal of Marine Science, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Mind the gap - The need to integrate novel plankton methods alongside ongoing long-term monitoring - Matthew M. Holland; Luis Felipe Artigas; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Dafne Eerkes-Medrano; Marie Johansen; David G. Johns; Margarita Machairopoulou; Sophie Pitois; James Scott; et al. (Ocean & Coastal Management, 2025)

Per- and poly-fluoroalkyl substances (PFAS) do not accumulate with age or affect population survival in ruddy turnstone (Arenaria interpres) - Tobias A. Ross; Junjie Zhang; Tonje G. Skaalvik; Robyn Atkinson; Roz Jessop; Alexandros G. Asimakopoulos; Veerle L.B. Jaspers; Marcel Klaassen (Science of The Total Environment, 2024)

Shorebirds Are Shrinking and Shape‐Shifting: Declining Body Size and Lengthening Bills in the Past Half‐Century - A. McQueen; M. Klaassen; G. J. Tattersall; S. Ryding; R. Atkinson; R. Jessop; C. J. Hassell; M. Christie; A. Fröhlich; M. R. E. Symonds (Ecology Letters, 2024)
Animals are predicted to shrink and shape‐shift as the climate warms, declining in size, while their appendages lengthen. Determining which types of species are undergoing these morphological changes, and why, is critical to understanding species responses to global change, including potential adaptation to climate warming. We examine body size and bill length changes in 25 shorebird species using extensive field data (> 200,000 observations) collected over 46 years (1975–2021) by community scientists. We show widespread body size declines over time, and after short‐term exposure to warmer summers. Meanwhile, shorebird bills are lengthening over time but shorten after hot summers. Shrinking and shape‐shifting patterns are consistent across ecologically diverse shorebirds from tropical and temperate Australia, are more pronounced in smaller species and vary according to migration behaviour. These widespread morphological changes could be explained by multiple drivers, including adaptive and maladaptive responses to nutritional stress, or by thermal adaptation to climate warming.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A natural mutant kumquat fruit with abnormal oil glands shows lower volatile production, better fruit flavor and higher resistance to postharvest disease - Man Zhu; Yang Wang; Zhebin Zeng; Xi Wu; Jiacheng Teng; Jingzong Zhang; Qianrong Han; Qiaoli Ma; Chuanwu Chen; Yunjiang Cheng; Xiuxin Deng; Niels J. Nieuwenhuizen; et al. (Postharvest Biology and Technology, 2024)

Long‐term shifts in phenology, thermal niche, population size, and their interactions in marine pelagic copepods - Stefano Corona; Andrew G. Hirst; David Atkinson; Jasmin Renz; Maarten Boersma; Angus Atkinson (Limnology and Oceanography, 2024)
Under climatic warming many species shift their seasonal timing of life cycle events (phenology) and seasonal abundance distribution, but whether they maintain the same thermal niche is still poorly understood. Here, we studied multidecadal trends in abundance and phenology of seven major copepod species across three stations (Stonehaven (SH), Helgoland Roads (HR), and Plymouth L4) on the North–West European shelf, spanning ~ 6.5° of latitude. All seven species consistently occupied colder temperatures at the northern station compared to the southerly station, but they maintained the same realized thermal niche over years. Expected phenological shifts (i.e., earlier when warmer) in some stations were obscured possibly by the long‐term drop of copepod density in spring–summer, which may be due to a variation in the food/predators abundance. The ongoing spring–summer declines in abundance (~ 50%) of many North Atlantic pelagic species over the last five decades, as found in recent studies, may have also influenced the metrics of seasonal timing. To separate the seasonal timing of life events from that of seasonal abundance distribution, we used a time series of egg production rate (EPR) of Calanus helgolandicus at L4, and found that this shifted later into the summer–autumn over the last 30 yr of warming, coincident with declining spring–summer food and increasing predator abundance. Overall, direct temperature effects do appear to influence the seasonal timing of the copepods, but to explain impacts at individual stations or long‐term trends in population size or phenology, understanding the changing balance of food and predators appears to be critical.

Responses of intraspecific metabolic scaling to temperature and activity differ between water‐ and air‐breathing ectothermic vertebrates - Guillermo García‐Gómez; Andrew G. Hirst; Matthew Spencer; David Atkinson (Ecology Letters, 2024)
Metabolism underpins all life‐sustaining processes and varies profoundly with body size, temperature and locomotor activity. A current theory explains some of the size‐dependence of metabolic rate (its mass exponent, b ) through changes in metabolic level ( L ). We propose two predictive advances that: (a) combine the above theory with the evolved avoidance of oxygen limitation in water‐breathers experiencing warming, and (b) quantify the overall magnitude of combined temperatures and degrees of locomotion on metabolic scaling across air‐ and water‐breathers. We use intraspecific metabolic scaling responses to temperature (523 regressions) and activity (281 regressions) in diverse ectothermic vertebrates (fish, reptiles and amphibians) to show that b decreases with temperature‐increased L in water‐breathers, supporting surface area‐related avoidance of oxygen limitation, whereas b increases with activity‐increased L in air‐breathers, following volume‐related influences. This new theoretical integration quantitatively incorporates different influences (warming, locomotion) and respiration modes (aquatic, terrestrial) on animal energetics.

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Assessment of contaminants, health and survival of migratory shorebirds in natural versus artificial wetlands – The potential of wastewater treatment plants as alternative habitats - Tobias A. Ross; Junjie Zhang; Michelle Wille; Tomasz Maciej Ciesielski; Alexandros G. Asimakopoulos; Prescillia Lemesle; Tonje G. Skaalvik; Robyn Atkinson; Roz Jessop; Veerle L.B. Jaspers; Marcel Klaassen (Science of The Total Environment, 2023)

Long-term exposure to traffic-related air pollution and stroke: A systematic review and meta-analysis - P. Haddad; M. Kutlar Joss; J. Weuve; D. Vienneau; R. Atkinson; J. Brook; H. Chang; F. Forastiere; G. Hoek; R. Kappeler; F. Lurmann; S. Sagiv; et al. (International Journal of Hygiene and Environmental Health, 2023)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Biotic factors limit the invasion of the plague pathogen ( Yersinia pestis ) in novel geographical settings - Henry G. Fell; Owen G. Osborne; Matthew D. Jones; Steve Atkinson; Simon Tarr; Suzanne H. Keddie; Adam C. Algar (Global Ecology and Biogeography, 2022)
Aim The distribution of Yersinia pestis , the pathogen that causes plague in humans, is reliant upon transmission between host species; however, the degree to which host species distributions dictate the distribution of Y. pestis , compared with limitations imposed by the environmental niche of Y. pestis per se, is debated. We test whether the present‐day environmental niche of Y. pestis differs between its native range and an invaded range and whether biotic factors (host distributions) can explain observed discrepancies. Location North America and Central Asia. Major taxa studied Yersinia pestis . Methods We use environmental niche models to determine whether the current climatic niche of Y. pestis differs between its native range in Asia and its invaded range in North America. We then test whether the inclusion of information on the distribution of host species improves the ability of models to capture the North American niche. We use geographical null models to guard against spurious correlations arising from spatially autocorrelated occurrence points. Results The current climatic niche of Y. pestis differs between its native and invaded regions. The Asian niche overpredicted the distribution of Y. pestis across North America. Including biotic factors along with the native climatic niche increased niche overlap between the native and invaded models, and models containing only biotic factors performed better than the native climatic niche alone. Geographical null models confirmed that the increased niche overlap through inclusion of biotic factors did not, with a couple of exceptions, arise solely from spatially autocorrelated occurrences. Main conclusions The current climatic niche in Central Asia differs from the current climatic niche in North America. Inclusion of biotic factors improved the fit of models to the Y. pestis distribution data in its invaded region better than climate variables alone. This highlights the importance of host species when investigating zoonotic disease introductions and suggests that climatic variables alone are insufficient to predict disease distribution in novel environments.

Increasing nutrient stress reduces the efficiency of energy transfer through planktonic size spectra - Angus Atkinson; Martin K.S. Lilley; Andrew G. Hirst; Andrea J. McEvoy; Glen A. Tarran; Claire Widdicombe; Elaine S. Fileman; E. Malcolm S. Woodward; Katrin Schmidt; Tim J. Smyth; Paul J. Somerfield (Limnology and Oceanography, 2021)
Size‐spectral approaches quantify the efficiency of energy transfer through food webs, but theory and field studies disagree over how changes in temperature, nutrients, and extreme weather impact on this efficiency. We address this at two scales: via 6 years of weekly sampling of the plankton size spectrum at the Plymouth L4 shelf sea site, and via a new, global‐scale, meta‐analysis of aquatic size spectra. The time series showed that with summertime nutrient starvation, the energy transfer efficiency from picoplankton to macroplankton decreased (i.e., steepening slopes of the size spectra). This reflected increasing dominance by small cells and their microbial consumers. The extreme storms in winter 2013/2014 caused high metazoan mortality, steep size‐spectral slopes, and reduced plankton biomass. However, recovery was within months, demonstrating an inbuilt resilience of the system. Both L4 and our meta‐analysis showed steep slopes of normalized size spectra (median −1.11). This reflects much lower values, either of trophic transfer efficiency (3.5%) or predator–prey mass ratio (569), compared to commonly quoted values. Results from the meta‐analysis further showed that to represent energy transfer faithfully, size spectra are best constructed in units of carbon mass and not biovolume, and span a mass range of > 10 7 . When this range is covered, both the meta‐analysis and time series show a dome‐shaped relationship between spectral slopes and plankton biomass, with steepening slopes under increasingly oligotrophic and eutrophic conditions. This suggests that ocean warming could decrease the efficiency of energy transfer through pelagic food webs via indirect effects of increasing stratification and nutrient starvation.

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Increasing picocyanobacteria success in shelf waters contributes to long‐term food web degradation - Katrin Schmidt; Antony J. Birchill; Angus Atkinson; Robert J. W. Brewin; James R. Clark; Anna E. Hickman; David G. Johns; Maeve C. Lohan; Angela Milne; Silvia Pardo; Luca Polimene; Tim J. Smyth; et al. (Global Change Biology, 2020)
Continental margins are disproportionally important for global primary production, fisheries and CO 2 uptake. However, across the Northeast Atlantic shelves, there has been an ongoing summertime decline of key biota—large diatoms, dinoflagellates and copepods—that traditionally fuel higher tropic levels such as fish, sea birds and marine mammals. Here, we combine multiple time series with in situ process studies to link these declines to summer nutrient stress and increasing proportions of picophytoplankton that can comprise up to 90% of the combined pico‐ and nanophytoplankton biomass in coastal areas. Among the pico‐fraction, it is the cyanobacterium Synechococcus that flourishes when iron and nitrogen resupply to surface waters are diminished. Our field data show how traits beyond small size give Synechococcus a competitive edge over pico‐ and nanoeukaryotes. Key is their ability to grow at low irradiances near the nutricline, which is aided by their superior light‐harvesting system and high affinity to iron. However, minute size and lack of essential biomolecules (e.g. omega‐3 polyunsaturated fatty acids and sterols) render Synechococcus poor primary producers to sustain shelf sea food webs efficiently. The combination of earlier spring blooms and lower summer food quantity and quality creates an increasing period of suboptimal feeding conditions for zooplankton at a time of year when their metabolic demand is highest. We suggest that this nutrition‐related mismatch has contributed to the widespread, ~50% decline in summer copepod abundance we observe over the last 60 years. With Synechococcus clades being prominent from the tropics to the Arctic and their abundances increasing worldwide, our study informs projections of future food web dynamics in coastal and shelf areas where droughts and stratification lead to increasing nutrient starvation of surface waters.

Evidence for a novel subcortical mechanism for posterior cingulate cortex atrophy in HIV peripheral neuropathy - John R. Keltner; Alan Tong; Eelke Visser; Mark Jenkinson; Colm G. Connolly; Alyssa Dasca; Aleks Sheringov; Zachary Calvo; Earl Umbao; Rohit Mande; Mary Beth Bilder; Gagandeep Sahota; et al. (Journal of NeuroVirology, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Lifeform indicators reveal large‐scale shifts in plankton across the North‐West European shelf - Jacob Bedford; Clare Ostle; David G. Johns; Angus Atkinson; Mike Best; Eileen Bresnan; Margarita Machairopoulou; Carolyn A. Graves; Michelle Devlin; Alex Milligan; Sophie Pitois; Adam Mellor; et al. (Global Change Biology, 2020)
Increasing direct human pressures on the marine environment, coupled with climate‐driven changes, is a concern to marine ecosystems globally. This requires the development and monitoring of ecosystem indicators for effective management and adaptation planning. Plankton lifeforms (broad functional groups) are sensitive indicators of marine environmental change and can provide a simplified view of plankton biodiversity, building an understanding of change in lower trophic levels. Here, we visualize regional‐scale multi‐decadal trends in six key plankton lifeforms as well as their correlative relationships with sea surface temperature (SST). For the first time, we collate trends across multiple disparate surveys, comparing the spatially and temporally extensive Continuous Plankton Recorder (CPR) survey (offshore) with multiple long‐term fixed station‐based time‐series (inshore) from around the UK coastline. These analyses of plankton lifeforms showed profound long‐term changes, which were coherent across large spatial scales. For example, ‘diatom’ and ‘meroplankton’ lifeforms showed strong alignment between surveys and coherent regional‐scale trends, with the 1998–2017 decadal average abundance of meroplankton being 2.3 times that of 1958–1967 for CPR samples in the North Sea. This major, shelf‐wide increase in meroplankton correlated with increasing SSTs, and contrasted with a general decrease in holoplankton (dominated by small copepods), indicating a changing balance of benthic and pelagic fauna. Likewise, inshore‐offshore gradients in dinoflagellate trends, with contemporary increases inshore contrasting with multi‐decadal decreases offshore (approx. 75% lower decadal mean abundance), urgently require the identification of causal mechanisms. Our lifeform approach allows the collation of many different data types and time‐series across the NW European shelf, providing a crucial evidence base for informing ecosystem‐based management, and the development of regional adaptation plans.

Long-Term Change of Demersal Fish Assemblages on the Inshore Agulhas Bank Between 1904 and 2015 - Jock C. Currie; Lara J. Atkinson; Kerry J. Sink; Colin G. Attwood (Frontiers in Marine Science, 2020)

Psychopathological symptoms associated with synthetic cannabinoid use: a comparison with natural cannabis - Vincent T. Mensen; Annabel Vreeker; Johan Nordgren; Amanda Atkinson; Rafael de la Torre; Magi Farré; Johannes G. Ramaekers; Tibor M. Brunt (Psychopharmacology, 2019)

First report of luminous stimuli eliciting sound production in weevils - Carol L. Bedoya; Ximena J. Nelson; Michael Hayes; Richard W. Hofstetter; Thomas H. Atkinson; Eckehard G. Brockerhoff (The Science of Nature, 2019)

A synthesis of major environmental-body size clines of the sexes within arthropod species - Curtis R. Horne; Andrew G. Hirst; David Atkinson (Oecologia, 2019)

Biomass distribution of fishes and mussels mediates spatial and temporal heterogeneity in nutrient cycling in streams - Garrett W. Hopper; Keith B. Gido; Caryn C. Vaughn; Thomas B. Parr; Traci G. Popejoy; Carla L. Atkinson; Kiza K. Gates (Oecologia, 2018)

Mortality of Calanus helgolandicus : Sources, differences between the sexes and consumptive and nonconsumptive processes - Jacqueline L. Maud; Andrew G. Hirst; Angus Atkinson; Penelope K. Lindeque; Andrea J. McEvoy (Limnology and Oceanography, 2018)
While losses from mortality are as important as gains from reproduction in zooplankton population dynamics, the former are more challenging to quantify. We used two approaches to provide complementary insights into the mortality of a biomass‐dominant copepod, Calanus helgolandicus , at Station L4 in the English Channel. Using a neutral‐red staining method, we found that dead carcasses represented a mean of 9% of the C. helgolandicus copepodites sampled. The resulting nonconsumptive mortality rates are the first that have been derived for C. helgolandicus ; and estimates suggest a contribution of 0–54% (median of 4.4%) to the total mortality rate. Consumptive mortality (i.e., that due to removal by predation), dominated for most of the year and contributed a mean of 89% to total mortality. Nonconsumptive mortality increased during summer and winter, and was positively related to maximum wind speed during the preceding 72 h, indicating that extreme weather events may lead to increased mortality. Using the Vertical Life Table approach, mortality rates across the CV‐adult male stage pair were on average ∼ 2.5 times greater than those of CV‐adult females. Adult male consumptive mortality rates were ∼ 6 times greater than those for females; adult male nonconsumptive rates were twice those of females, suggesting that predation is of greater significance to male loss rates. Summer CV‐adult mortality rates were positively correlated to temperature, and to the abundance of predatory chaetognaths and siphonophores, suggesting that the gelatinous predator assemblage is the dominant agent for population control of late stage copepodites of C. helgolandicus at L4.

Long-term change in epibenthic assemblages at the Prince Edward Islands: a comparison between 1988 and 2013 - C. E. O. von der Meden; L. J. Atkinson; G. M. Branch; S. Asdar; I. J. Ansorge; M. van den Berg (Polar Biology, 2017)

The potential role of Antarctic krill faecal pellets in efficient carbon export at the marginal ice zone of the South Orkney Islands in spring - A. Belcher; G. A. Tarling; C. Manno; A. Atkinson; P. Ward; G. Skaret; S. Fielding; S. A. Henson; R. Sanders (Polar Biology, 2017)

Occurrence of two novel actinospore types (Cnidaria: Myxosporea) in Brazilian fish farms, and the creation of a novel actinospore collective group, Seisactinomyxon - Tiago Milanin; Stephen D. Atkinson; Márcia R.M. Silva; Roberto G. Alves; Antônio A.M. Maia; Edson A. Adriano (Acta Parasitologica, 2017)
The involvement of oligochaetes in the life cycles of fresh water myxozoan parasites in Brazil was investigated. Of 333 oligochaetes collected in a fish farm in the State of São Paulo, three (0.9%) released Aurantiactinomyxon type spores. From 86 worms collected in a fish farm in Mato Grosso do Sul State, 1 (0.9%) released actinospores with a novel morphology for which we propose the name Seisactinomyxon. Infected oligochaetes were identified by morphology: all belonged to family Naididae, with

Ontogenetic body‐mass scaling of nitrogen excretion relates to body surface area in diverse pelagic invertebrates - A. G. Hirst; M. K. S. Lilley; D. S. Glazier; D. Atkinson (Limnology and Oceanography, 2017)
Many physiological and ecological processes depend on body size and the supply of limiting nutrients. Hence, it is important to derive quantitative predictions based on a mechanistic understanding of the influence of body size on metabolic rate and on the ratios of consumed to excreted elements. Among diverse pelagic invertebrates that change shape during ontogeny, recent analysis has demonstrated a significant positive correlation between the body‐mass allometry of respiration rates (measured as the ontogenetic body mass‐scaling exponent b R ) and the allometry of body surface area ( b A , as predicted from body‐shape changes using a Euclidean model). As many pelagic invertebrates use a large portion of their external body surface for both resource uptake and waste excretion, we predicted that body‐mass scaling exponents for rates of excretion of soluble N ( b N ) should also then relate to the degree of body‐shape change during growth. We tested this hypothesis using literature data on b N for 39 species of pelagic invertebrates across five different phyla, and find strong support: b N is significantly positively correlated with predicted b A , whilst also co‐varying with b R . Intraspecific differences between b N and b R values reveal ontogenetic shifts in the ratio of O 2 ‐consumed to N‐excreted. We suggest that a variety of factors, including adaptive developmental shifts in the relative anabolism and catabolism of proteins and lipids, may cause these shifts in consumption–excretion ratios. Diverse pelagic invertebrates that dominate vast open water ecosystems falsify the predictions of general metabolic scaling theories built upon resource‐transport networks, but support predictions of surface‐area dependent theory.

Information infrastructure for Australia’s Integrated Marine Observing System - Marton G. Hidas; Roger Proctor; Natalia Atkins; Julian Atkinson; Laurent Besnard; Peter Blain; Philip Bohm; Jon Burgess; Kim Finney; Dan Fruehauf; Guillaume Galibert; Xavier Hoenner; et al. (Earth Science Informatics, 2016)

A global synthesis of seasonal temperature–size responses in copepods - Curtis R. Horne; Andrew G. Hirst; David Atkinson; Aitana Neves; Thomas Kiørboe (Global Ecology and Biogeography, 2016)
Aim Body size is a master trait with significant ecological importance. Seasonal changes in body size within diverse ectothermic species can result from different environmental conditions experienced during ontogeny in subsequent generations. Whilst intraspecific changes in adult size have been well studied under controlled experimental conditions and across geographical ranges, comprehensive analyses of temporal changes are lacking, and there remains considerable unexplained variation in body size responses within aquatic taxa. Using planktonic copepods as an exemplar taxon, we quantify variation in adult body mass within seasonally varying marine and freshwater environments. We describe how size variation relates to temperature, food concentration (chlorophyll‐ a ) and life‐history characteristics, including feeding strategy. Location Global. Methods Using a meta‐analytic approach we extract quantitative data from published literature on seasonal size responses of copepods. We analyse competing models to determine the best predictors of these responses, and compare the relative importance of temperature and chlorophyll‐ a concentration in explaining variation in body size. Results We quantify 140 seasonal size responses from 33 different global locations, representing 48 planktonic copepod species from four taxonomic orders. We find that temperature ( r 2 = 0.50), rather than food ( r 2 = 0.22), is the dominant explanatory variable of changes in adult body size across seasons. A striking outcome is that calanoid copepods, which utilize feeding currents to capture prey, exhibit a four‐fold greater reduction in adult body mass per °C (−3.66%) compared with cyclopoid copepods (−0.91%), which are ambush feeders. By contrast, species body size or reproductive strategy did not explain variation in the seasonal temperature–size response. Main conclusions Our findings lead us to suggest that feeding strategies may play a significant role in dictating the magnitude of seasonal temperature–size responses in copepods, with potential implications for other ectotherms with diverse feeding methods. Seasonal temperature–size responses were typically much more variable than responses in laboratory studies that provided excess food, suggesting that field conditions modify the temperature–size response.

Seismically induced landslide hazard and exposure modelling in Southern California based on the 1994 Northridge, California earthquake event - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Landslides, 2015)

Erratum to: Earthquake-and-landslide events are associated with more fatalities than earthquakes alone - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Natural Hazards, 2015)

A systematic review of landslide probability mapping using logistic regression - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Landslides, 2015)

Temperature‐size responses match latitudinal‐size clines in arthropods, revealing critical differences between aquatic and terrestrial species - Curtis R. Horne; Andrew. G. Hirst; David Atkinson (Ecology Letters, 2015)
Two major intraspecific patterns of adult size variation are plastic temperature‐size (T‐S) responses and latitude‐size (L‐S) clines. Yet, the degree to which these co‐vary and share explanatory mechanisms has not been systematically evaluated. We present the largest quantitative comparison of these gradients to date, and find that their direction and magnitude co‐vary among 12 arthropod orders ( r 2 = 0.72). Body size in aquatic species generally reduces with both warming and decreasing latitude, whereas terrestrial species have much reduced and even opposite gradients. These patterns support the prediction that oxygen limitation is a major controlling factor in water, but not in air. Furthermore, voltinism explains much of the variation in T‐S and L‐S patterns in terrestrial but not aquatic species. While body size decreases with warming and with decreasing latitude in multivoltine terrestrial arthropods, size increases on average in univoltine species, consistent with predictions from size vs. season‐length trade‐offs.

Influence of nocturnal and daytime sleep on initial orthostatic hypotension - N. C. S. Lewis; H. Jones; P. N. Ainslie; A. Thompson; K. Marrin; G. Atkinson (European Journal of Applied Physiology, 2015)

Ground Motion Prediction Equations in the San Jacinto Fault Zone: Significant Effects of Rupture Directivity and Fault Zone Amplification - I. Kurzon; F. L. Vernon; Y. Ben-Zion; G. Atkinson (Pure and Applied Geophysics, 2014)

Body shape shifting during growth permits tests that distinguish between competing geometric theories of metabolic scaling - Andrew G. Hirst; Douglas S. Glazier; David Atkinson (Ecology Letters, 2014)
Metabolism fuels all of life's activities, from biochemical reactions to ecological interactions. According to two intensely debated theories, body size affects metabolism via geometrical influences on the transport of resources and wastes. However, these theories differ crucially in whether the size dependence of metabolism is derived from material transport across external surfaces, or through internal resource‐transport networks. We show that when body shape changes during growth, these models make opposing predictions. These models are tested using pelagic invertebrates, because these animals exhibit highly variable intraspecific scaling relationships for metabolic rate and body shape. Metabolic scaling slopes of diverse integument‐breathing species were significantly positively correlated with degree of body flattening or elongation during ontogeny, as expected from surface area theory, but contradicting the negative correlations predicted by resource‐transport network models. This finding explains strong deviations from predictions of widely adopted theory, and underpins a new explanation for mass‐invariant metabolic scaling during ontogeny in animals and plants.

Accounting for the Impact of Conservation on Human Well‐Being - E.J. MILNER‐GULLAND; J.A. MCGREGOR; M. AGARWALA; G. ATKINSON; P. BEVAN; T. CLEMENTS; T. DAW; K. HOMEWOOD; N. KUMPEL; J. LEWIS; S. MOURATO; B. PALMER FRY; et al. (Conservation Biology, 2014)
Conservationists are increasingly engaging with the concept of human well‐being to improve the design and evaluation of their interventions. Since the convening of the influential Sarkozy Commission in 2009, development researchers have been refining conceptualizations and frameworks to understand and measure human well‐being and are starting to converge on a common understanding of how best to do this. In conservation, the term human well‐being is in widespread use, but there is a need for guidance on operationalizing it to measure the impacts of conservation interventions on people. We present a framework for understanding human well‐being, which could be particularly useful in conservation. The framework includes 3 conditions; meeting needs, pursuing goals, and experiencing a satisfactory quality of life. We outline some of the complexities involved in evaluating the well‐being effects of conservation interventions, with the understanding that well‐being varies between people and over time and with the priorities of the evaluator. Key challenges for research into the well‐being impacts of conservation interventions include the need to build up a collection of case studies so as to draw out generalizable lessons; harness the potential of modern technology to support well‐being research; and contextualize evaluations of conservation impacts on well‐being spatially and temporally within the wider landscape of social change. Pathways through the smog of confusion around the term well‐being exist, and existing frameworks such as the Well‐being in Developing Countries approach can help conservationists negotiate the challenges of operationalizing the concept. Conservationists have the opportunity to benefit from the recent flurry of research in the development field so as to carry out more nuanced and locally relevant evaluations of the effects of their interventions on human well‐being. Consideración del Impacto de la Conservación sobre el Bienestar Humano

Earthquake-and-landslide events are associated with more fatalities than earthquakes alone - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Natural Hazards, 2014)

Cooperation between scientists, NGOs and industry in support of sustainable fisheries: the South African hake Merluccius spp. trawl fishery experience a - J. G. Field; C. G. Attwood; A. Jarre; K. Sink; L. J. Atkinson; S. Petersen (Journal of Fish Biology, 2013)
This paper examines the increasingly close interaction between natural and social scientists, non‐governmental organizations (NGO) and industry, in pursuit of responsible ecosystem‐based management of fisheries. South Africa has committed to implementing an ecosystem approach to fisheries management. Management advice stems from multi‐stakeholder representation on government‐led scientific and management working groups. In the hake Merluccius capensis and Merluccius paradoxus fishery, the primary management measure is an annual total allowable catch ( TAC ), the level of which is calculated using a management procedure ( MP ) that is revised approximately every 4 years. Revision of the MP is a consultative process involving most stakeholders, and is based on simulation modelling of projected probable scenarios of resource and fishery dynamics under various management options. NGOs , such as the Worldwide Fund for Nature in South Africa (WWF‐SA), have played an important role in influencing consumers, the fishing industry and government to develop responsible fishing practices that minimize damage to marine ecosystems. Cooperation between industry, government and scientists has helped to improve sustainability and facilitated the meeting of market‐based incentives for more responsible fisheries. Research includes ecosystem modelling, spatial analysis and ecosystem risk assessment with increasing research focus on social and economic aspects of the fishery. A four‐year cooperative experiment to quantify the effect of trawling on benthic community structure is being planned. The food requirements of top predators still need to be included in the TAC ‐setting formulae and more social and economic research is needed. This paper also demonstrates how NGO initiatives such as Marine Stewardship Council certification and the Southern African Sustainable Seafood Initiative, a traffic light system of classifying seafood for consumers, have contributed to responsible fishing practices, increased ecosystem research and public awareness. This fishery appears to have a good future, provided that the monitoring, control and surveillance systems continue to function, TACs remain within ecologically sustainable limits and the effective collaboration between government, industry, scientists and NGOs continues to drive positive change.

A meta-analytic approach to quantify the dose–response relationship between melatonin and core temperature - K. Marrin; B. Drust; W. Gregson; G. Atkinson (European Journal of Applied Physiology, 2013)

An enzyme activity capable of endotransglycosylation of heteroxylan polysaccharides is present in plant primary cell walls - Sarah L. Johnston; Roneel Prakash; Nancy J. Chen; Monto H. Kumagai; Helen M. Turano; Janine M. Cooney; Ross G. Atkinson; Robert E. Paull; Roshan Cheetamun; Antony Bacic; David A. Brummell; Roswitha Schröder (Planta, 2013)

Species distribution modeling of storm-petrels (Oceanodroma furcata and O. leucorhoa) in the North Pacific and the role of dimethyl sulfide - G. R. W. Humphries; F. Huettmann; G. A. Nevitt; C. Deal; D. Atkinson (Polar Biology, 2012)

Super-resolution mapping using Hopfield Neural Network with panchromatic imagery - Quang Minh Nguyen; Peter M. Atkinson; Hugh G. Lewis (International Journal of Remote Sensing, 2011)

Diurnal variation in the salivary melatonin responses to exercise: relation to exercise-mediated tachycardia - K. Marrin; B. Drust; W. Gregson; C. J. Morris; N. Chester; G. Atkinson (European Journal of Applied Physiology, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Short-term coherency between gross primary production and community respiration in an algal-dominated reef flat - J. L. Falter; M. J. Atkinson; D. W. Schar; R. J. Lowe; S. G. Monismith (Coral Reefs, 2011)

Cadmium, Copper, Iron, and Zinc Concentrations in Kidneys of Grey Wolves, Canis lupus, from Alaska, Idaho, Montana (USA) and the Northwest Territories (Canada) - S. R. Hoffmann; S. A. Blunck; K. N. Petersen; E. M. Jones; J. C. Koval; R. Misek; J. A. Frick; H. D. Cluff; C. A. Sime; M. McNay; K. B. Beckman; M. W. Atkinson; et al. (Bulletin of Environmental Contamination and Toxicology, 2010)

Discussion of the paper by I. Sass and U. Burbaum entitled “A method for assessing adhesion of clays to tunneling machines” (doi:10.1007/s10064-008-0178-6) - J. H. Atkinson; P. G. Fookes (Bulletin of Engineering Geology and the Environment, 2010)

The Challenges of Dewatering at the Victor Diamond Mine in Northern Ontario, Canada - L. C. Atkinson; P. G. Keeping; J. C. Wright; Houmao Liu (Mine Water and the Environment, 2010)

The influence of defined ante-mortem stressors on the early post-mortem biochemical processes in the abdominal muscle of the Norway lobster, Nephrops norvegicus (Linnaeus, 1758) - Sebastian G. Gornik; Amaya Albalat; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2010)

Applying the HAZUS-MH software tool to assess seismic risk in downtown Ottawa, Canada - S. K. Ploeger; G. M. Atkinson; C. Samson (Natural Hazards, 2010)

Geostatistically estimated image noise is a function of variance in the underlying signal - A. Asmat; P. M. Atkinson; G. M. Foody (International Journal of Remote Sensing, 2010)

Effect of capture method on the physiology and nucleotide breakdown products in the Norway lobster ( Nephrops norvegicus ) - Amaya Albalat; Sebastian G. Gornik; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2009)

Production of transgenic pineapple (Ananas cosmos (L.) Merr.) plants via adventitious bud regeneration - M.-L. Wang; G. Uruu; L. Xiong; X. He; C. Nagai; K. T. Cheah; J. S. Hu; G.-L. Nan; B. S. Sipes; H. J. Atkinson; P. H. Moore; K. G. Rohrbach; et al. (In Vitro Cellular & Developmental Biology - Plant, 2009)

Estimating per‐pixel thematic uncertainty in remote sensing classifications - K. M. Brown; G. M. Foody; P. M. Atkinson (International Journal of Remote Sensing, 2009)

Modelling geometric and misregistration error in airborne sensor data to enhance change detection - K. M. Brown; G. M. Foody; P. M. Atkinson (International Journal of Remote Sensing, 2007)

Microhomologies between T-DNA ends and target sites often occur in inverted orientation and may be responsible for the high frequency of T-DNA-associated inversions - Andreas E. Müller; Ross G. Atkinson; Robert B. Sandoval; Richard A. Jorgensen (Plant Cell Reports, 2007)

Idiopathic muscle necrosis in the Norway lobster, Nephrops norvegicus (L.): aetiology, pathology and progression to bacteraemia - I D Ridgway; G D Stentiford; A C Taylor; R J A Atkinson; T H Birkbeck; D M Neil (Journal of Fish Diseases, 2007)
The pathology and progression of idiopathic muscle necrosis (IMN) in Nephrops norvegicus and possible aetiologies have been investigated. Trawl capture, aerial exposure and handling initiate IMN, and the condition can be induced through periods of aerial exposure alone, in the absence of trawling. Within 24–48 h after trawl capture IMN progresses to a multi‐species bacterial septicaemia, with moribund animals exhibiting clinical signs. The aetiology of this condition has been examined using molecular (16S rRNA gene sequencing) and biochemical (standard taxonomic assays, Biolog TM ) criteria to characterize bacterial isolates from moribund and healthy animals. Histopathology of the IMN phase reveals a loss of sarcomeric structure with necrotic lesions containing pyknotic nuclei, fragments of myofibrils and connective tissue elements. In the bacterial phase there is extensive loss of abdominal muscle structure, and the presence of rod‐shaped Gram‐negative bacteria in the degrading tissues. The results demonstrate that the IMN condition is connected to stressful conditions imposed on N. norvegicus , but involves no pathogenic agents. This is followed by an opportunistic bacterial infection that causes further tissue spoilage. It is believed that the primary cause of both IMN and bacteraemia is imposed stress, but they are expressed in different time courses.

ASSESSING KILLER WHALE PREDATION ON STELLER SEA LIONS FROM FIELD OBSERVATIONS IN KENAI FJORDS, ALASKA - John M. Maniscalco; Craig O. Matkin; Daniela Maldini; Donald G. Calkins; Shannon Atkinson (Marine Mammal Science, 2007)
The behavioral and predatory patterns of Gulf of Alaska (GOA) transient killer whales ( Orcinus orca ) were studied between 2000 and 2005 using remote video and vessel‐based observations near the Chiswell Island Steller sea lion ( Eumetopias jubatus ) rookery and in the broader Kenai Fjords (KF) region of the northern GOA. GOA transient killer whales were observed on 118 d over the 6‐yr period; the median group size was two (range: 1–9). Nine predation events were observed from vessels and an additional sixteen were inferred from remote video studies; all involved Steller sea lions. Estimates from field observations suggest that fifty‐nine sea lions were consumed over the summer seasons of 2002–2005; whereas estimates based on published caloric requirements of transient killer whales would suggest a loss of 103 sea lions over the same time period. GOA transients spent a large proportion (43%) of their time resting which may be a strategy for conserving energy. Predation on sea lion pups at the Chiswell Island rookery was greatest during years when a single killer whale was foraging alone and when a 1.5‐yr‐old calf was evidently being trained to handle prey. Predation on pups was low during years when killer whales were foraging in groups and were observed and presumed to be taking mostly juvenile sea lions. Our study suggests that GOA transients are having a minor effect on the recovery of Steller sea lions in the GOA.

Effects of nonlocal turbulence on the mass transfer of dissolved species to reef corals - James L. Falter; Marlin J. Atkinson; Ryan J. Lowe; Stephen G. Monismith; Jeffrey R. Koseff (Limnology and Oceanography, 2007)
We examined the importance of nonlocal turbulence to the mass transfer of dissolved species from both cylinders and models of reef coral. Solid gypsum cylinders and gypsum‐coated model coral were dissolved in an outdoor flume at mean flow speeds of 4.5 and 10 cm s −1 . Three model corals were used: two branched forms of the genera Acropora and Pocillopora , and one lobate form of the genus Platygyra . Turbulence intensities (Tu) were measured as the ratio of the standard deviation of the time‐variant flow to the mean. Tu of between 5% and 55% were created independently of the mean flow by pumping water through two vertical arrays of jets. Mass transfer coefficients increased by 10‐70% with turbulence intensity for all forms at both mean flow speeds considered ( p

LeMAN4 endo-β-mannanase from ripe tomato fruit can act as a mannan transglycosylase or hydrolase - Roswitha Schröder; Teresa F. Wegrzyn; Neelam N. Sharma; Ross G. Atkinson (Planta, 2006)

Transformation of Actinidia eriantha: A potential species for functional genomics studies in Actinidia - Tianchi Wang; Yidong Ran; Ross G. Atkinson; Andrew P. Gleave; Dan Cohen (Plant Cell Reports, 2006)

Glioma: What is the role of c-Myc, hsp90 and telomerase? - A. Shervington; N. Cruickshanks; H. Wright; R. Atkinson-Dell; R. Lea; G. Roberts; L. Shervington (Molecular and Cellular Biochemistry, 2006)

Pre-maturity α-amylase and incipient sprouting in UK winter wheat, with special reference to the variety Rialto - A. F. Tjin Wong Joe; R. W. Summers; G. D. Lunn; M. D. Atkinson; P. S. Kettlewell (Euphytica, 2005)

Spatial variability of factors influencing coastal change in the Western Canadian Arctic - G. K. Manson; S. M. Solomon; D. L. Forbes; D. E. Atkinson; M. Craymer (Geo-Marine Letters, 2005)

Trimethyltin-induced neurogenesis in the murine hippocampus - G. Jean Harry; Christopher A. McPherson; Robert N. Wine; Kelly Atkinson; Christian Lefebvre d'Hellencourt (Neurotoxicity Research, 2003)

The incidence and diversity of Wolbachia in gallwasps (Hymenoptera; Cynipidae) on oak - A. Rokas; R. J. Atkinson; J.‐L. Nieves‐Aldrey; S. A. West; G. N. Stone (Molecular Ecology, 2002)
Wolbachia bacteria infect ≈ 20% of all insect species, and cause a range of alterations to host reproduction, including imposition of thelytoky. The incidence and phenotypic impact of Wolbachia remains to be established in many insect taxa, and considerable research effort is currently focused on its association with particular reproductive modes and the relative importance of the various pathways via which infection occurs. Gallwasps represent an attractive system for addressing these issues for two reasons. First, they show a diversity of reproductive modes (including arrhenotoky, thelytoky and cyclical parthenogenesis) in which the impact of Wolbachia infection can be examined. Second, they occupy two intimately linked trophic niches (gall‐inducers and inquilines) between which there is potential for the horizontal exchange of Wolbachia infection. In the arrhenotokous gallwasp lineages screened to date (the herb‐galling ‘Aylacini’ and the rose‐galling Diplolepidini), Wolbachia infection always induces thelytoky. The impact of Wolbachia in other arrhenotokous clades, and in the cyclically parthenogenetic clades remains unknown. Here we use polymerase chain reaction (PCR) screening and sequence data for two Wolbachia genes ( wsp and ftsZ ) to examine the prevalence and incidence of Wolbachia infection in 64 species (a total of 609 individuals) in two further tribes: the arrhenotokous inquilines (tribe Synergini), and the cyclically parthenogenetic oak gallwasps (tribe Cynipini). We ask: (i) whether Wolbachia infection has any apparent impact on host reproduction in the two tribes and (ii) whether there is any correlation between Wolbachia infection and the apparent lack of an arrhenotokous generation in many oak gallwasp life cycles. We show: (i) that Wolbachia infection is rare in the Cynipini. Infected species show no deviation from cyclical parthenogenesis, and infection is no more common in species known only from a thelytokous generation; (ii) that there is a higher incidence of infection within the arrhenotokous inquilines, and generally in gallwasp tribes without cyclical parthenogensis; (iii) all Wolbachia ‐positive inquiline species are known to possess males, implying either that Wolbachia infection does not result in loss of sex in this tribe or, more probably, that (as for some rose gallwasps) Wolbachia infection leads to loss of sex in specific populations; and (iv) although we find some inquilines and gall inducers to be infected with Wolbachia having the same wsp sequence, these hosts are not members of the same gall communities, arguing against frequent horizontal transmission between these two trophic groups. We suggest that exchange may be mediated by the generalist parasitoids common in oak galls.

Sucrose Phosphate Synthase Genes in Plants Belong to Three Different Families - Georg Langenkämper; Raymond W.M. Fung; Richard D. Newcomb; Ross G. Atkinson; Richard C. Gardner; Elspeth A. MacRae (Journal of Molecular Evolution, 2002)

MDH1: an apple homeobox gene belonging to the BEL1 family - Yi-Hu Dong; Jia-Long Yao; Ross G. Atkinson; Joanna J. Putterill; Bret A. Morris; Richard C. Gardner (Plant Molecular Biology, 2000)

Polygalacturonase gene expression in kiwifruit: relationship to fruit softening and ethylene production - Zhong-Yan Wang; Elspeth A. MacRae; Michele A. Wright; Karen M. Bolitho; Gavin S. Ross; Ross G. Atkinson (Plant Molecular Biology, 2000)

Transition Regimes in Valley Airflows - J-G. Li; B. W. Atkinson (Boundary-Layer Meteorology, 1999)

Apple ACC-oxidase and polygalacturonase: ripening-specific gene expression and promoter analysis in transgenic tomato - Ross G. Atkinson; Karen M. Bolitho; Michele A. Wright; Teresa Iturriagagoitia-Bueno; Suzanne J. Reid; Gavin S. Ross (Plant Molecular Biology, 1998)

An integrated genetic linkage map of the laboratory rat - Donna M. Brown *, , Tara C. Matise; George Koike; Jason S. Simon; Eric S. Winer; Sarah Zangen; Michael G. McLaughlin; Masahide Shiozawa; O. Scott Atkinson; James R. Hudson, Jr.; Aravinda Chakravarti; Eric S. Lander **, , Howard (Mammalian Genome, 1998)

GUS expression patterns from a tobacco yellow dwarf virus-based episomal vector - P. D. Needham; R. G. Atkinson; B. A. M. Morris; R. C. Gardner; A. P. Gleave (Plant Cell Reports, 1998)

Expression of an engineered cysteine proteinase inhibitor (Oryzacystatin-IΔD86) for nematode resistance in transgenic rice plants - P. Vain; B. Worland; M. C. Clarke; G. Richard; M. Beavis; H. Liu; A. Kohli; M. Leech; J. Snape; P. Christou; H. Atkinson (Theoretical and Applied Genetics, 1998)

Biochemical and molecular characterisation of xyloglucan endotransglycosylase from ripe kiwifruit - R. Schröder; R. G. Atkinson; G. Langenkämper; R. J. Redgwell (Planta, 1998)

In situ hybridization in Actinidia using repeat DNA and genomic probes - G. Yan; R. G. Atkinson; A. R. Ferguson; M. A. McNeilage; B. G. Murray (Theoretical and Applied Genetics, 1997)

Spatial and temporal patterns in the activity of European moles - D. W. Macdonald; R. P. D. Atkinson; G. Blanchard (Oecologia, 1997)

The allopolyploid origin of kiwifruit,Actinidia deliciosa (Actinidiaceae) - Ross G. Atkinson; Guido Cipriani; David J. Whittaker; Richard C. Gardner (Plant Systematics and Evolution, 1997)

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)